2020
DOI: 10.1210/clinem/dgaa935
|View full text |Cite
|
Sign up to set email alerts
|

Distant Metastases From Childhood Differentiated Thyroid Carcinoma: Clinical Course and Mutational Landscape

Abstract: Context Distant metastases (DM) from childhood differentiated thyroid carcinoma (DTC) are uncommon and published studies are limited. Objective This work aimed to describe the outcomes of patients with DM from childhood DTC and to evaluate the molecular landscape of these tumors. Methods A retrospective study was conducted at a tertiary cancer center includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 67 publications
(143 reference statements)
3
40
1
Order By: Relevance
“…A report from a US referral center on 148 pediatric DTC with DM found a persistent disease rate of 93% after a median follow up of 10.5 years [29], and this striking difference compared to our results, despite a similar median administered cumulative activities of radioiodine, may rely on different evaluation criteria used for treatment response. We have previously shown that in adult patients who had no residual imaging abnormalities after RAI treatment for DM, the residual Tg level (detectable or not) had no predictive role on subsequent progression [16].…”
Section: Discussioncontrasting
confidence: 81%
“…A report from a US referral center on 148 pediatric DTC with DM found a persistent disease rate of 93% after a median follow up of 10.5 years [29], and this striking difference compared to our results, despite a similar median administered cumulative activities of radioiodine, may rely on different evaluation criteria used for treatment response. We have previously shown that in adult patients who had no residual imaging abnormalities after RAI treatment for DM, the residual Tg level (detectable or not) had no predictive role on subsequent progression [16].…”
Section: Discussioncontrasting
confidence: 81%
“…One of the major biases of pediatric DTC guidelines is the paucity of specific data and studies available, despite the fact that the peculiarity of the presentation, prognosis, and management of DTC in children has been clarified [4][5][6]. Thus, extrapolating and applying results from studies of adult population in pediatric field might lead to equivocal conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…At the onset DTC, pediatric patients have higher risk of cervical lymph node and lung metastases, when compared to the adult counterpart [3]. However, the prognosis is favorable, and the mortality rate is very low [4][5][6]. In this particular setting, customizing the risk of relapse of each patient may avoid unbeneficial treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The genomic landscape of pediatric thyroid disease is quickly emerging. Recent literature suggests that fusion mutations are more common in the primary tumor of pediatric thyroid cancer and may portend a more aggressive clinical course (5). The limited genomic data in this cohort support this theory.…”
Section: Cancer Is Evolvingmentioning
confidence: 68%
“…In addition, many patients (n = 148) had persistent disease despite RAI. This finding was echoed in a recent large retrospective study wherein 93% of children and young adults with metastatic thyroid cancer had persistent disease despite RAI (5). Fortunately, patients in both cohorts experienced very low disease-specific mortality.…”
Section: Cancer Is Evolvingmentioning
confidence: 89%